A ten-year review of ESBL and non-ESBL Escherichia Coli Bloodstream infections among children at a tertiary referral hospital in South Africa - Malande, Oliver Ombeva (Department of Paediatrics and Child Health, 2020)
Introduction: Bloodstream infection (BSI) is an important cause of morbidity and mortality in children (1). There are few descriptions of Escherichia coli (E. coli) BSI in children, particularly in Africa, yet E. coli is increasing in importance as a cause of antibiotic-resistant infection in paediatric settings. Methods: In this retrospective, descriptive study aspects of E. coli BSI epidemiology are described over a 10-year period including incidence risk, risk factors for extended spectrum β-lactamase (ESBL)- producing E. coli BSI, antibiotic susceptibility of the bacterial isolates and outcome including risk factors for severe disease. Results: There were 583 new E. coli BSI episodes among 217,483 admissions, an overall incidence risk of 2.7 events/1,000 hospital admissions. Of 455 of these E. coli BSI episodes that were analysed, 136 (29.9%) were caused by ESBL-producing isolates. Risk factors for ESBL-producing E. coli BSI included hospitalization in the 28-day period preceding E. coli BSI episodes and having an underlying chronic illness other than HIV infection at the time of the E. coli BSI. None of the E. coli isolates were resistant to carbapenems or colistin. The mortality rate was 5.9% and admission to the intensive care unit was required in 12.3% of BSI episodes. Predictors of severe disease included age less than 1 month, hospitalization in the 28-day period preceding E. coli BSI and BSI without a definable focus. Conclusions: These findings extend our understanding of E. coli BSI in a sub-Saharan African setting, provide useful information that can guide empiric treatment choices for community- and hospitalacquired BSI and help inform prevention strategies.